CARBON TRADING MEETS SHARIA RETHINKING CAP AND TRADE AND OFFSET FOR SUSTAINABLE FUTURES - Bella Pridaningsih; Wahyu Akbar (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study analyzes the compliance of Cap and Trade and Offset transaction mechanisms in Indonesia’s carbon trading with the principles of Islamic commercial jurisprudence (fiqh muamalah) using a qualitative descriptive and normative-sharia analysis. The focus includes ownership rights over carbon as intangible assets, clarity of transaction objects, transparency in emission calculations through the MRV (Monitoring, Reporting, Verification) system, and avoidance of gharar, riba, and maisir elements. The findings show that both mechanisms are Shariah-compliant under strict supervision by the Financial Services Authority (OJK) and international certification. Indonesian regulations, especially Presidential Regulation No. 98 of 2021, reinforce market integrity and align with maqashid shariah, particularly in environmental preservation and social justice. Policy recommendations include strengthening the Sharia Supervisory Board, synergy between fatwa authorities and regulators, and improved Sharia literacy among market participants. Overall, carbon trading mechanisms have the potential to be strategic instruments for sustainable development consistent with Islamic principles.